Prescription opioid analgesics for pain management in Australia: 20 years of dispensing - Islam, M.; McRae, I.; Mazumdar, S.; Taplin, S.; McKetin, Rebecca (Blackwell Publishing, 2016)
Background: Opioid prescribing/dispensing data can inform policy surrounding regulation by informing trends and types of opioid prescribed and geographic variations. In Australia so far only partial data on dispensing have been published, and data for states/territories remain unknown. Aim: Using a range of measures, this study examines 20-year (1992–2011) trends in prescription opioid analgesics in Australia – both nationally and for individual jurisdictions. Methods: Dispensing data were obtained from the Drug Utilisation Sub-Committee and the Pharmaceutical Benefits Scheme (PBS) websites. Trends in numbers of prescriptions and daily defined dose (DDD)/1000 people/day were examined over time and across states/territories. Seasonal variations in PBS/Repatriation Pharmaceutical Benefits Scheme (RPBS) items for nationwide dispensing were adjusted using a centred moving smoothing technique. Results: In two decades, 165.32 million prescriptions for opioids were dispensed, with codeine and its derivatives the most prescribed formulation (50.1%) followed by tramadol (13.5%) and oxycodone derivatives (12.7%). In terms of DDD/1000 people/day, dispensing increased from 5.38 in 1992 to 14.46 in 2011. There are significant increasing trends for total, PBS/RPBS and under co-payment prescriptions (priced below patient co-payment). The DDD/1000 people/day for items dispensed through PBS/RPBS was highest in Tasmania. Conclusion: Prescription opioid dispensing increased substantially over the study period. With an ageing population, this trend is likely to continue in future. A growing concern about harms associated with opioid use warrants balanced control measures so that harms could be minimised without reducing effective pain treatment. Research examining utilisation in small geographic areas may help design spatially tailored interventions. A real-time drug-monitoring programme may reduce undue prescribing and dispensing.